Characterization of Novel Broad-Host-Range Bacteriophage DLP3 Specific to Stenotrophomonas maltophilia as a Potential Therapeutic Agent - Peters, Danielle L.; McCutcheon, Jaclyn G.; Dennis, Jonathan J. (Frontiers in Microbiology, 2020)
A novel Siphoviridae phage specific to the bacterial species Stenotrophomonas maltophilia was isolated from a pristine soil sample and characterized as a second member of the newly established Delepquintavirus genus. Phage DLP3 possesses one of the broadest host ranges of any S. maltophilia phage yet characterized, infecting 22 of 29 S. maltophilia strains. DLP3 has a genome size of 96,852 bp and a G+C content of 58.4 %, which is significantly lower than S. maltophilia host strain D1571 (G+C content of 66.9 %). The DLP3 genome encodes 153 coding domain sequences covering 95 % of the genome, including five tRNA genes with different specificities. The DLP3 lysogen exhibits a growth rate increase during the exponential phase of growth as compared to the wild type strain. DLP3 also encodes a functional erythromycin resistance protein, causing lysogenic conversion of the host D1571 strain. Although a temperate phage, DLP3 demonstrates excellent therapeutic potential because it exhibits a broad host range, infects host cells through the S. maltophilia type IV pilus, and exhibits lytic activity in vivo. Undesirable traits, such as its temperate lifecycle, can be eliminated using genetic techniques to produce a modified phage useful in the treatment of S. maltophilia bacterial infections.